Local and Global Cultural Interaction: Representation in Asian Video Games as a Medium of Cultural Communication - Gusanti, Yurina (MD Research Center, 2025)
This study aims to explore the influence of cultural representation in video games on players' perceptions in the context of globalization. Using a qualitative approach and literature study, this research analyzes relevant literature on how video games integrate cultural elements from various countries and affect players' views of other cultures. Data is collected from various articles, journals, and books discussing themes such as cultural representation, globalization, and player interaction in video games. The results indicate that video games function as a medium that enables players to engage with foreign cultures through visual elements, narrative, and gameplay. Furthermore, the study finds that video games can introduce cultural elements previously unknown to players, while simultaneously shaping their perceptions of those cultures. These findings provide new insights into how video games can serve as a tool for expanding intercultural understanding, reducing stereotypes, and enhancing cultural dialogue in the era of globalization. The implications of this research suggest that video games have the potential to create spaces for more inclusive and profound cultural exchange. The study also opens opportunities for further research examining the social and cultural impacts of video games, particularly in the context of globalization's influence on the gaming industry and players' perceptions of foreign cultures.